Comparison of sutureless and sutured circumcision in pediatric populations: A systematic review - Muhammad Ikhsan Farhan; Jufriady Ismy; Ahmad Fauzan; Vannisa Fadya (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Circumcision is one of the most commonly performed pediatric surgical procedures and is traditionally closed using absorbable sutures. However, conventional suturing may increase postoperative pain, edema, infection risk, foreign-body reactions, and cosmetic irregularities. Sutureless techniques, including cyanoacrylate-based tissue adhesives and clamp-assisted methods, have emerged as minimally invasive alternatives that may improve wound healing and reduce complications. Purpose: To systematically compare the safety, procedural efficiency, cosmetic outcomes, and postoperative pain associated with sutureless versus conventional sutured circumcision in pediatric populations. Method: This systematic review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A comprehensive literature search was performed using PubMed, Wiley, and Google Scholar databases. Study quality and risk of bias were evaluated using the Revised Tool for Risk of Bias in Randomized Trials (ROB 2). Three eligible comparative studies were included in the final analysis. Results: Sutureless circumcision demonstrated several advantages over conventional sutured techniques, including shorter operative time, fewer postoperative complications, and superior cosmetic outcomes. Most suture-related adverse events, such as local irritation and foreign-body reactions, were reported exclusively in the sutured groups. In addition, patients undergoing sutureless procedures generally experienced lower postoperative pain scores. Conclusion: Sutureless circumcision using cyanoacrylate adhesives appears to be a safe and effective alternative to traditional sutured closure, offering improved procedural efficiency and postoperative outcomes. Nevertheless, the current evidence is limited by small sample sizes, heterogeneous study populations, and non-standardized outcome measures. Further large-scale, well-designed comparative studies are needed to establish robust clinical recommendations.